Mathematics of investment - Altares, Priscilla S.; Arce, Ma. Teresa B.; Aquino, Abner A.; Howe, Asuncion B.; Laddaran, Angeline T.; Mananquil, Claro T.; Sy, Evangeline Agueda G. ; Tizon, Helen D.; Yao, Ana Maria S.; Villanueva, Antonio (Manila, 2003)
This book is designed to provide business administration and accountancy students theories of investments and applications of interest and annuities
Keywords: Business mathematics; Investment